2001
DOI: 10.1210/jc.86.7.3097
|View full text |Cite
|
Sign up to set email alerts
|

Novel Patterns of Gene Expression in Pituitary Adenomas Identified by Complementary Deoxyribonucleic Acid Microarrays and Quantitative Reverse Transcription-Polymerase Chain Reaction

Abstract: Pituitary adenomas account for approximately 10% of intracranial tumors, but little is known of the oncogenesis of these tumors. The identification of tumor-specific genes may further elucidate the pathways of tumor formation. We used complementary DNA microarrays to examine gene expression profiles in nonfunctioning, PRL, GH, and ACTH secreting adenomas, compared with normal pituitary. Microarray analysis showed that 128 of 7075 genes examined were differentially expressed. We then analyzed three genes with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 0 publications
4
74
0
1
Order By: Relevance
“…BAG1 expression in GH-secreting tumours), when judged by RQ-PCR validation on the larger group of tumours (Table 1). A demonstration of the robust nature of this novel technology is the remarkable similarity of the results compared with RQ-PCR results from the cDNA array study published by Evans and colleagues (9): they showed (i) that MERTK was over-expressed in ACTH-secreting adenomas up to 13-fold, but was under-expressed in PRL-secreting adenomas, (ii) that the FR gene was over-expressed in NFPAs up to 30-fold, but was under-expressed in Table 1 Side-by-side comparison of the expression profiles of the genes LAPTM4B, BAG1 and p18 as measured by (1) GH-and PRL-secreting adenomas; and (iii) that the ODC1 gene was over-expressed in GH-secreting adenomas compared with other tumour types but not normal pituitary, but was under-expressed in ACTHsecreting adenomas compared with normal, GH-secreting adenomas and NFPAs (9). On the Affymetrix GeneChip HG-U133A array MERTK was over-expressed in ACTH-secreting adenomas 6.4-fold, and underexpressed 2.5-fold in PRL-secreting tumours, whereas the FR was over-expressed in NFPAs 13-fold and underexpressed in GH-and ACTH-secreting adenomas (2.1-and 2.3-fold respectively); there was a trend towards under-expression in the PRL-secreting adenomas (1.69-fold), but it did not meet our cut-off criterion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BAG1 expression in GH-secreting tumours), when judged by RQ-PCR validation on the larger group of tumours (Table 1). A demonstration of the robust nature of this novel technology is the remarkable similarity of the results compared with RQ-PCR results from the cDNA array study published by Evans and colleagues (9): they showed (i) that MERTK was over-expressed in ACTH-secreting adenomas up to 13-fold, but was under-expressed in PRL-secreting adenomas, (ii) that the FR gene was over-expressed in NFPAs up to 30-fold, but was under-expressed in Table 1 Side-by-side comparison of the expression profiles of the genes LAPTM4B, BAG1 and p18 as measured by (1) GH-and PRL-secreting adenomas; and (iii) that the ODC1 gene was over-expressed in GH-secreting adenomas compared with other tumour types but not normal pituitary, but was under-expressed in ACTHsecreting adenomas compared with normal, GH-secreting adenomas and NFPAs (9). On the Affymetrix GeneChip HG-U133A array MERTK was over-expressed in ACTH-secreting adenomas 6.4-fold, and underexpressed 2.5-fold in PRL-secreting tumours, whereas the FR was over-expressed in NFPAs 13-fold and underexpressed in GH-and ACTH-secreting adenomas (2.1-and 2.3-fold respectively); there was a trend towards under-expression in the PRL-secreting adenomas (1.69-fold), but it did not meet our cut-off criterion.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy are unclear, but may possibly be due to error from small differences in fluorescence values at low levels, as the actual expression value of p18 in the normal pituitary was below the median expression value and therefore expression levels in the tumours were even lower. It is interesting to note that in their study Evans and colleagues (9) also showed less good correlation between microarray and RQ-PCR results when genes were under-expressed as opposed to when they were overexpressed (9). Members of the INK4 family of CDK inhibitors, which includes p16 (INK4A) and p18 (INK4C), specifically bind to CDK4 and CDK6, and prevent cyclin D-dependent phosphorylation of retinoblastoma and progression through the cell cycle.…”
Section: Rq-pcrmentioning
confidence: 97%
See 1 more Smart Citation
“…The RT cDNA reaction products were subjected to realtime quantitative PCR (SYBR Green PCR Core kit; PerkinElmer) with primers for IL-8 (Invitrogen, Carlsbad, CA) and 18s ribosomal RNA (PerkinElmer) as previously described (14). The IL-8 expression level was normalized to the 18s rRNA level of the same sample.…”
Section: Real-time Quantitative Rt-pcr (Qrt-pcr) Analysis Of Il-8 Mrnamentioning
confidence: 99%
“…One previous study demonstrated that FR-targeted boron-10 containing carbon nanoparticles were specifically taken up by HeLa cells, an FR expressing cell line [14]. Other previous studies have also reported that FR was uniquely overexpressed in NFPAs but was not expressed by FPAs or normal pituitary glands cells [15,27]. It is worthwhile to determine whether a FR-targeted boron agent could be used in BNCT for NFPAs, especially invasive NFPAs that are refractory to standard therapy.…”
Section: Discussionmentioning
confidence: 99%